2019
DOI: 10.1186/s10194-019-1017-9
|View full text |Cite
|
Sign up to set email alerts
|

Advances in genetics of migraine

Abstract: BackgroundMigraine is a complex neurovascular disorder with a strong genetic component. There are rare monogenic forms of migraine, as well as more common polygenic forms; research into the genes involved in both types has provided insights into the many contributing genetic factors. This review summarises advances that have been made in the knowledge and understanding of the genes and genetic variations implicated in migraine etiology.FindingsMigraine is characterised into two main types, migraine without aur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
172
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(174 citation statements)
references
References 261 publications
(299 reference statements)
2
172
0
Order By: Relevance
“…Clinical overlap among the three diseases has been reported. 30 However, EA2 mutations can be missense, truncating or cause aberrant splicing of CACNA1A, usually leading to loss-of-function and decreased Ca 2+ influx. On the other side, SCA6 mutations are usually small expansions of a polyglutamine in the C-terminal of the gene, which are responsible for accumulation of mutant Cav2.1 channels and selective degeneration of Purkinje cells.…”
Section: Chronic Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical overlap among the three diseases has been reported. 30 However, EA2 mutations can be missense, truncating or cause aberrant splicing of CACNA1A, usually leading to loss-of-function and decreased Ca 2+ influx. On the other side, SCA6 mutations are usually small expansions of a polyglutamine in the C-terminal of the gene, which are responsible for accumulation of mutant Cav2.1 channels and selective degeneration of Purkinje cells.…”
Section: Chronic Symptomsmentioning
confidence: 99%
“…On the other side, SCA6 mutations are usually small expansions of a polyglutamine in the C-terminal of the gene, which are responsible for accumulation of mutant Cav2.1 channels and selective degeneration of Purkinje cells. 30 ATP1A2 gene is localised on chromosome 1q23.2. It encodes the a2 subunit of the glial sodium-potassium ATPase pump.…”
Section: Chronic Symptomsmentioning
confidence: 99%
“…For instance, a review conducted to see the relationship between headache and epilepsy reported the comorbidity of headache and epilepsy as a result of common genetic mutations and clinical features [18,19], but the suggested link is not revealed conclusive evidence of a real causal association [20]. Further, studies also suggested that there are genetic relationships [19] as well as common underlying pathophysiological mechanisms including the imbalance between excitatory and inhibitory neurotransmitters in epilepsy and headache, especially for migraine [18,21]. Proposed theories for shared etiologies include ion channel dysfunction, glutamatergic mechanisms, and mitochondrial dysfunction [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Migraine is a multifactorial disorder with a complex of mechanisms engaged in its pathogenesis [1,14,15]. That is why there is no single treatment that would be effective in every migraineur.…”
Section: Migraine and Plant Antioxidantsmentioning
confidence: 99%